Conventional Teaching and an Interactive-Based Teaching Methods to adjust Learners’ Grammar and Speaking Competence in English Classrooms: A Comparative Study for effectiveness methods in learning - Waode Hanafiah (Universitas Sulawesi Barat, 2022)
The study discusses the effectiveness of Conventional Teaching Method utilizing whole-class member group and an Interactive-based Teaching Method employing small group works for improving both learners’ Grammar and Speaking competences in English Grammar classrooms. Data were taken from 68 first-year students of English Education Department of UNIDAYAN University, Bau-Bau, South-East Sulawesi province, who sit in a pre-test and post-test of two English competences; Grammar and Speaking in English. The research design is quasi experimental assigning 5 group works as the independent variables and 2 English competences; Grammar and Speaking in English as the dependent variables. The group works consist of various number of students. The treatment of all group works were reduplicated twice. The study reveals that the interactive-based teaching method utilizing small group works is far more effective for improving both learners’ Grammar and Speaking competences compared to those of conventional teaching method employing whole-class member group work in English Grammar classroom. The learners’ mean achievement is 25.04 points and 8.8 points respectively. The t-test confirms that there is a significant difference between the two methods. Moreover, the less the number of group members the more effective to the achievement of the learning target of the classrooms.